The Relationship Between Maternal Work Duration, Caregiver Involvement, and Picky Eating Behavior Among Toddlers Aged 1-3 Years in Bekasi City - Aulia Rahmawati; Agung Nugroho; Siti Fadhilahtun Nasriyah (Al-Hijrah Indonesia, 2026)
Picky eating behavior is a common nutritional challenge among toddlers, characterized by a strong preference for specific foods and the rejection of novel items. This study aimed to examine the relationship between maternal work duration and caregiver involvement with picky eating behavior among toddlers aged 1–3 years in Bekasi City. Employing a quantitative cross-sectional design, data were collected via online questionnaires from 174 mothers selected through convenience sampling. Data were analyzed using the Chi-square test with a 95% confidence level (α = 0.05). The results indicated a high prevalence of picky eating (71.8%), with slightly higher proportions observed among children of mothers who worked long hours and across all caregiver involvement categories. However, statistical analysis revealed no significant relationship between maternal work duration (p=0.255) or caregiver involvement (p=0.179) and picky eating behavior. These findings suggest that picky eating is a complex, multifactorial issue not solely dictated by maternal employment hours or basic caregiver involvement metrics. In conclusion, fostering healthy eating habits requires comprehensive strategies involving both parents and caregivers. Community health practitioners must prioritize promoting responsive feeding practices and positive mealtime environments rather than merely focusing on maternal work schedules.